2012
DOI: 10.1111/j.1755-3768.2011.02313.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that convergence rather than accommodation controls intermittent distance exotropia

Abstract: . Purpose:  This study considered whether vergence drives accommodation or accommodation drives vergence during the control of distance exotropia for near fixation. High accommodative convergence to accommodation (AC/A) ratios are often used to explain this control, but the role of convergence to drive accommodation (the CA/C relationship) is rarely considered. Atypical CA/C characteristics could equally, or better, explain common clinical findings. Methods:  Nineteen distance exotropes, aged 4–11 years, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 31 publications
1
39
1
1
Order By: Relevance
“…Convergence, binocular disparity, blur and proximity cues have all been described as being responsible for driving accommodation. 5,20,21 The differing strength or influence of these cues may be another reason for the difference between the results of two methods.…”
Section: Discussionmentioning
confidence: 99%
“…Convergence, binocular disparity, blur and proximity cues have all been described as being responsible for driving accommodation. 5,20,21 The differing strength or influence of these cues may be another reason for the difference between the results of two methods.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, and perhaps more logically, our research has found that all the intermittent exotropes we studied converge to control. 28 Most intermittent exotropes appear to be 'disparity people' and are no more reliant on blur cues than the general population. They appear to converge to overcome their primary large exodeviation, which then may bring along additional accommodation, so they actually accommodate a bit more than typical children and some may even over-accommodate.…”
Section: Intermittent Exotropes Do Not 'Use Accommodation To Control'mentioning
confidence: 99%
“…Furthermore, there is more recently published evidence that challenges our basic assumptions about the relationship between accommodation and convergence in general and how it affects the behaviour of the visual axes in certain types of patients, in particular how it may not actually be accommodation but rather vergence that allows control of the deviation at near in IDEX. 13 If these findings are supported by further evidence, then we really do need to re-evaluate our basic understanding of the role the AC/A ratio plays in the diagnosis and management of strabismus.…”
Section: Impact On Diagnosis and Managementmentioning
confidence: 99%
“…This has been refuted 12,13 on the basis that unless the amount of actual accommodation is measured, with an autorefractor for example, only an assumption can be made about how much accommodation is physically exerted or relaxed through concave and convex lenses. Fig.…”
Section: Choice Of Methodsmentioning
confidence: 99%